Structural Basis of RICs Iron Donation for Iron-Sulfur Cluster Biogenesis - Silva, Liliana S. O.; Matias, Pedro M.; Romão, Célia V.; Saraiva, Lígia M. (Frontiers in Microbiology, 2021)
Escherichia coli YtfE is a di-iron protein of the widespread Repair of Iron Centers proteins (RIC) family that has the capacity to donate iron, which is a crucial component of the biogenesis of the ubiquitous family of iron-sulfur proteins. In this work we identify in E. coli a previously unrecognized link between the YtfE protein and the major bacterial system for iron-sulfur cluster (ISC) assembly. We show that YtfE establishes protein-protein interactions with the scaffold IscU, where the transient cluster is formed, and the cysteine desulfurase IscS. Moreover, we found that promotion by YtfE of the formation of an Fe-S cluster in IscU requires two glutamates, E125 and E159 in YtfE. Both glutamates form part of the entrance of a protein channel in YtfE that links the di-iron center to the surface. In particular, E125 is crucial for the exit of iron, as a single mutation to leucine closes the channel rendering YtfE inactive for the build-up of Fe-S clusters. Hence, we provide evidence for the key role of RICs as bacterial iron donor proteins involved in the biogenesis of Fe-S clusters.